CONTEMPORARY TRENDS AND INNOVATIONS IN SCULPTURE IN UZBEKISTAN : EXPLORING THE INTERSECTION OF TRADITION AND MODERNITY - Alimardon Khaydaraliyevich Abdullaev (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific article explores the evolving landscape of modern sculpture in Uzbekistan, a country steeped in rich cultural heritage and a crossroads of historical influences. Focusing on contemporary sculptural practices, the study investigates the dynamic interplay between traditional Uzbek artistry and emerging trends in sculpture, reflecting the societal changes and artistic developments within the region. By examining the works of prominent Uzbek sculptors and institutions, we shed light on the diverse approaches, materials, themes, and dimensions that modern sculpture in Uzbekistan encompasses. This exploration underscores the country’s cultural legacy while embracing global artistic influences.